Biogenic synthesis of silver nanoparticles using pigment producing Streptomyces sp and Its drug binding assay - Krishnamoorthy, Santhanalakshmi; Ekambaram, Natarajan (International Journal of Scientific Research in Biological Sciences, 2018)
Cardiovascular disease, management of hypertension is mostly treated by Amlodipine, atorvastatin and telmisartan. Amikacin also one of the pharmaceutical drugs against bacterial infections. The Streptomyces sp. DSK2 melanin absorbs the drugs in different concentration, different temperature and different incubation timings. The result shows that the Streptomyces sp. DSK2melanin absorb the drugs in 40◦C and the reaction timings were 180min. Amlodopine bind strongly at 40◦C at180 min, other two drugs Atorvastatin and Amikacin moderate bind at 40◦C at 120 min. Other biomedical studies of the Streptomyces sp. DSK2 melanin silver nanoprticle was synthesized in 180s by the microwave radiation method. The silver nanoparticle range 50nm in size, which is confirmed by TEM analysis, UV spectrum at 420nm , FTIR Spectrum , XRD. The melanin showed the potent antioxidant activity was determined by DPPH assay, the maximum activity was 87.96 and the total antioxidant activity phosphomolybdate assay) was 88.05. in this study, Streptomyces sp. DSK2 Melanin has great biomedical activity.